An Effect of Work Stress and Work Motivation on Employee Performance During the Covid-19 Pandemic at PT. Fast Food Indonesia (Case Study of KFC Branch Elephant Mada Medan) - Kamaluddin; Hasrul Azwar Hasibuan; Russiadi (Britain International for Academic Research (BIAR) Publisher, 2022)
This study is to show and analyze the relationship between work stress and work motivation on employee performance during the current Covid 19 pandemic. The population in this study is PT Fast Food Indonesia Kentucky Fried Chicken (KFC) Gajah Mada Branch in Medan City. The number of samples in this study was 54 people who were employees of the company. with the analysis technique using multiple linear regression analysis. The results of the study (1) the results showed that partially the work stress variable had a positive and significant effect on employee performance at KFC Branch Gajah Mada. (2) The results showed that partially the work motivation variable had a positive and significant effect on employee performance at KFC Branch Gajah Mada.